PENGARUH MEDIASI PROFITABILITAS TERHADAP HUBUNGAN LEVERAGE DAN PENGHINDARAN PAJAK: STUDI DI PERUSAHAAN REAL ESTATE & PROPERTI YANG TERDAFTAR DI BEI - Erlianny, Vivin; Hutabarat, Francis M. (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACTProfitability and Leverage are tax avoidance factors that aim to increase profits, the researcher wants to examine and analyze the effect of profitability, leverage on tax avoidance with profitability and leverage as independent variables and tax avoidance dependent variables using secondary data and samples in the form of financial statements of 28 companies. Real Estate and Property listed on the IDX 20172018. Samples were taken using probability sampling techniques and analyzed using purpose sampling techniques. In this study using SPSS and it was found that profitability and leverage affect tax avoidance.